The use of sociodrama in learning about the concept of social organization in high school social studies - Madlangbayan, Kriemhilda Mejica 1936- (1977)
This seminar paper hopes to give both students and teachers of social studies an idea of how they can bring life to a classroom. The researcher worked on the hypothesis tha a sociodrama can stimulate student activity, critical thinking, and active participation. This is limited for the development of the concept of the social organization for first year high school social studies.